2018
DOI: 10.1155/2018/6495362
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybridization Approach between the Fireworks Algorithm and Grey Wolf Optimizer Algorithm

Abstract: The main aim of this paper is to present a new hybridization approach for combining two powerful metaheuristics, one inspired by physics and the other one based on bioinspired phenomena. The first metaheuristic is based on physics laws and imitates the explosion of the fireworks and is called Fireworks Algorithm; the second metaheuristic is based on the behavior of the grey wolf and belongs to swarm intelligence methods, and this method is called the Grey Wolf Optimizer algorithm. For this work we studied and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Singh et al [ 23 ] proposed an improved grey wolf optimization algorithm, which was used to solve the economic power load scheduling problem and achieved good results. Barraza et al [ 24 ] proposed a fusion algorithm based on FWA and GWO. The test of the benchmark function showed that the fusion algorithm had better performance.…”
Section: Related Workmentioning
confidence: 99%
“…Singh et al [ 23 ] proposed an improved grey wolf optimization algorithm, which was used to solve the economic power load scheduling problem and achieved good results. Barraza et al [ 24 ] proposed a fusion algorithm based on FWA and GWO. The test of the benchmark function showed that the fusion algorithm had better performance.…”
Section: Related Workmentioning
confidence: 99%
“…2018, [50] The aim of this hybridization was to combine the two most efficient algorithms, which have been inspired by physics and nature.…”
Section: Firework Algorithm (Fwa)mentioning
confidence: 99%
“…Implementing the GWO algorithm has been encouraging enough to merit further investigation as the GWO algorithm is used straight forward and can converge rapidly. Therefore, scientists and engineers, who are working on this field, are still under ways to improve GWO further (Mittal et al, 2016;Gao and Zhao, 2019;Wang et al, 2020;Barraza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%